Filipino Amerasians: Gauging Stigmatization, Intolerance and Hatemongering in a Pluralistic Asia Pacific Society - Peter C. Kutschera; Marie A. Caputi (Journal of Hate Studies, 2013)
Empirical and evidence-based researchers have neglected stigmatization, bias, name-calling, intolerance and even hatemongering experienced by military Filipino Amerasians and other biracial Pan Amerasian progeny who were abandoned abroad by their U.S. servicemen fathers. This condi- tion persists in the Philippines and has been reliably documented in other East and Southeast Asian nation-states, such as Japan, South Korea, and Vietnam. A relatively recent multiple-case study investigating psychosocial risk and mental health among Amerasians in Angeles, Pampanga, site of the former Clark Air Base, substantiated long-reported anecdotal claims that Anglo (White) and particularly African (Black) Amerasians were targets of victimization and traumatized by verbal harassment, hate, and occasional violence by mainstream Filipino natives or foreigners. These marginalized Amerasians faced stigmatization and ridicule because of skin color and pig- ment differences, uncommon facial features, hair texture variances and dif- ferential personal demeanors. Even more severe criticism was against Africans and Anglos because of the unproven, stereotypical view that the vast majority of Amerasian mothers were sex workers. For this reason, it was held that many servicemen rejected these children. The notion that within a pluralistic, multiracial society Filipino Amerasians experienced less discrimination and prejudice than might be expected within a more racially homogenous in part set the stage for the U.S. Citizen and Immigra- tion Services to diminish easements for Amerasians. In contrast to other nation-states where Amerasians reside (e.g., South Korea, Vietnam, Thai- land, and Cambodia), the belief is that stigmatization and its correlates are higher. However, these faulty conclusions take on exceptional geopolitical sensitivity in the realities that marginalized Amerasians face in the Philip- pines, a former U.S. colony and commonwealth.